2011
DOI: 10.1177/0894845310397361
|View full text |Cite
|
Sign up to set email alerts
|

Core Self-Evaluations, Career Decision Self-Efficacy, and Vocational Identity Among Greek Adolescents

Abstract: This study explored the mediating role of career decision self-efficacy between core self-evaluations (CSE), a newly established construct within the personality domain, and adolescents' vocational identity. Using a sample of 200 Greek high school students, it was found that for female adolescents CSE influenced vocational identity both directly and indirectly (via career decision self-efficacy). For male students, CSE had only an indirect effect on vocational identity through career decision self-efficacy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
5
32
1
9
Order By: Relevance
“…Consistent with the expectations of Hypothesis 1, the results of this study confirm that PIE mediates the relationship between hardiness and CDSE. Numerous previous studies have shown that CDSE can be predicted by a variety of personality constructs, including the Big Five personality traits (Bullock-Yowell et al, 2011;Hartman & Betz, 2007;Jin et al, 2009;Rogers et al, 2008), proactive personality (Hsieh & Huang, 2014), the healthy personality (Borgen & Betz, 2008), core self-evaluations (Koumoundourou et al, 2012), and the commitment component of personality hardiness (Niles & Sowa, 1992). However, few studies have dealt with the mechanisms through which personality traits relate to CDSE.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the expectations of Hypothesis 1, the results of this study confirm that PIE mediates the relationship between hardiness and CDSE. Numerous previous studies have shown that CDSE can be predicted by a variety of personality constructs, including the Big Five personality traits (Bullock-Yowell et al, 2011;Hartman & Betz, 2007;Jin et al, 2009;Rogers et al, 2008), proactive personality (Hsieh & Huang, 2014), the healthy personality (Borgen & Betz, 2008), core self-evaluations (Koumoundourou et al, 2012), and the commitment component of personality hardiness (Niles & Sowa, 1992). However, few studies have dealt with the mechanisms through which personality traits relate to CDSE.…”
Section: Discussionmentioning
confidence: 99%
“…Core self‐evaluation includes individual characteristics relative to a positive self‐concept in relation to intrapreneurship (i.e., self‐esteem, self‐efficacy, internal locus of control, low neuroticism; Muller et al, ; Ronen, ). In the literature, core self‐evaluation is positively associated with performance (Bono & Judge, ), employability (Judge & Hurst, ), career decision‐making self‐efficacy (Koumoundourou, Kounenou, & Siavara, ), and lack of career decision‐making difficulties (Di Fabio & Palazzeschi, ).…”
Section: Intrapreneurial Self‐capital: a New Career Constructmentioning
confidence: 99%
“…As stated previously, individuals with high proactive personality are relatively unconstrained by situational forces and thus should have a greater sense of self-determination and self-efficacy in their career lives. Practically, research has shown that CDSE can be predicted by a variety of personality constructs, including the healthy personality (Borgen & Betz, 2008), core self-evaluations (Koumoundourou, Kounenou, & Siavara, 2012), and the FFM traits (Bullock-Yowell et al, 2011;Hartman & Betz, 2007;Jin MARCH 2014• VoluMe 62 et al, 2009Rogers et al, 2008;Wang et al, 2006). Specifically, for the FFM traits-CDSE linkages, Wang et al (2006) found that extraversion affected CDSE positively for both White college students and college students of color, whereas neuroticism affected CDSE negatively for college students of color but not for White college students.…”
Section: Proactive Personality and Cdsementioning
confidence: 99%